Effect of exogenous melatonin on antioxidant properties and fruit softening of ‘Fengtang’ plum fruit (Prunus salicina Lindl.) during storage at room temperature - Zhang, Mingfei; Yang, Xinxia; Yin, Chunmei; Lin, Xingyu; Liu, Kexin; Zhang, Kexin; Su, Yujiao; Zou, Xu; Liao, Ling; Wang, Xun; He, Siya; He, Ruiyuan; et al. (Frontiers in Plant Science, 2024)
‘Fengtang’ plums soften quickly and lose flavor after harvest. This study comprehensively evaluated the effect of exogenous melatonin on the fruit quality of ‘Fengtang’ plums. According to our findings, exogenous melatonin prevented plum fruit from losing water, delayed the decline in firmness, and preserved a high TSS/TA level. Additionally, exogenous melatonin also enhanced the activity of antioxidant enzymes and increased the non-enzymatic antioxidants, thereby further increasing the antioxidant capacity of plum fruit. Notably, exogenous melatonin delayed the degradation of covalent soluble pectin (CSP), cellulose, and hemicellulose, as well as the rise in water-soluble pectin (WSP) concentration and the activity of cell wall degrading enzymes. Further investigation using atomic force microscopy (AFM) revealed that the chain-like structure of ionic-soluble pectin (ISP) and the self-assembly network structures of CSP were depolymerized, and melatonin treatment retarded the depolymerization of pectin structures. Our results showed that exogenous melatonin preserved the postharvest quality of plum fruits by controlling fruit softness and antioxidant capacity during storage.